ANALISIS PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN SEKSUAL BERBASIS INTERNET DITINJAU DARI HUKUM PIDANA DAN KEBIJAKAN KEAMANAN DIGITAL INDONESIA - Reny Okprianti; Nur Husni Emilson; Nurhaliza; Tatiana Erma Nova; Putri Yunita Rahmawati; Intan Dhea Ananda (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Developments in the field of information and communication technology have created great opportunities for online interaction, but have also increased the potential for sexual violence to occur on the internet. The aim of this research is to analyze how criminal law in Indonesia handles cases of sexual violence that occur online, examine the role of digital security policies in providing protection for victims, and evaluate how effective the regulations that have been implemented in the field are. Using a descriptive-analytical method, this study shows that legal instruments such as the Sexual Violence Crime Law, the Information and Electronic Transactions Law, and the Criminal Code have provided adequate normative foundations to ensnare perpetrators and protect victims. However, its effectiveness is still hampered by the limited ability of authorities to collect digital evidence, the community's low level of digital literacy, and a lack of coordination between the government, digital platforms and organizations assisting victims. Policies regarding digital security have a crucial role in prevention and recovery efforts, but their implementation is still not running optimally. This research emphasizes the importance of systemic strengthening through increasing apparatus capabilities, adaptive policy updates, cross-sector collaboration, and empowering victims to ensure comprehensive protection in the digital world.